Performance analysis of multi-legged systems - Silva, Manuel (2019)
This paper studies periodic gaits of multi-legged robot locomotion systems based on dynamic models. The purpose in to determine the system performance during walking and the best set of locomotion varibles that minimizes the optimization indices. For that objective the prescribed motion of the robot is completely characterized in terms of several locomotion variables such as gait, duty factor, body height, step length, stroke pitch, foot clearance, link lenghts, body and legs mass and cycle time. In this perspective, we formulate four performances measures of the walking robot namely, the locomobility of the foot, the mean absolute power, the mean power dispersion and the mean power lost in the joint actuators per walking distance. A set of model-based experimetns reveals the influence of the locomotion variables in the proposed indices.